Maintain or Shift? Focus on Inter-Ethnic Families in Indonesia - Sitinjak, Vivi Novalia; Harianja, Nurilam (TALENTA, 2022)
The study of mixed marriages is always an interesting topic to talk about, especially regarding the topic which is the impact of inter-ethnic mixed marriages. This study aims to describe the phenomenon of mixed marriages associated with the maintenance of traditional language. This paper applies qualitative research on language maintenance by Javanese-Batak Toba Families in Medan. The research data were derived from observation, interviews, and audio-recorded family conversations, parents’ role at home is the most dominant factor in maintaining vernacular language in inter-ethnic families, and vernacular language maintenance in inter-ethnic families is succeeded by language use at home and activities at home and surroundings while Javanese-Batak Toba families are patriarchy. The practices of vernacular language at home and in surroundings guide vernacular language maintenance (Pauwels,2016). The analysis displays that the relationship between culture, attitude, and prestige requires parents to maintain the vernacular language. Batak Toba language is maintained dominantly by families. Mother language is maintained. We conclude parents who have a positive attitude to their culture to show their prestige enforce children to maintain the vernacular language. This study recommends that further research explore vernacular language maintenance across three generations of Javanese-Batak Toba families.